2008
DOI: 10.1039/b718785h
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the fall of large atmospheric ice conglomerations: a multianalytical approach to the study of the Mejorada del Campo megacryometeor

Abstract: Certain local atmospheric anomalies, such as the formation of unusually large ice conglomerations (megacryometeors), have been proposed to be a potential natural hazard for people and aviation, as well as geoindicators for fingerprinting larger-scale atmospheric environmental changes. On March 13th 2007, at approximately 10:15 am, an ice chunk weighing about 10 kg fell from the clear-sky and crashed through the roof (around 15 m) of an industrial storage house in Mejorada del Campo, a town located 20 km east f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…These data are close to those obtained from the isotopic ratio measurements. Isotopic studies of megacryometeors (Martínez-Frías et al 2005;Martínez-Frías & Delgado 2006;Orellana et al 2008) confirmed that d 18 O and dD (Vienna Standard Mean Ocean Water, V-SMOW) of all samples fall into the Meteoric Water Line (MWL), demonstrating unequivocally that megacryometeors match well with typical tropospheric values (figure 6). The most positive values Although the spectral features in the OH stretching region are not very different among the megacryometeors observed, two groups can be established.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…These data are close to those obtained from the isotopic ratio measurements. Isotopic studies of megacryometeors (Martínez-Frías et al 2005;Martínez-Frías & Delgado 2006;Orellana et al 2008) confirmed that d 18 O and dD (Vienna Standard Mean Ocean Water, V-SMOW) of all samples fall into the Meteoric Water Line (MWL), demonstrating unequivocally that megacryometeors match well with typical tropospheric values (figure 6). The most positive values Although the spectral features in the OH stretching region are not very different among the megacryometeors observed, two groups can be established.…”
Section: Resultsmentioning
confidence: 78%
“…Isotopic studies of megacryometeors (Martínez-Frías et al 2005;Martínez-Frías & Delgado 2006;Orellana et al 2008) Martínez-Frías et al 2005. ) are typical of rain water in the Iberian Peninsula (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation